2003
DOI: 10.1046/j.1365-2125.2003.01993.x
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole, a novel wide‐spectrum triazole: oral pharmacokinetics and safety

Abstract: Aims Voriconazole is a potent new triazole with broad-spectrum antifungal activity against clinically significant and emerging pathogens. The present study evaluated the safety, toleration, and pharmacokinetics of oral voriconazole after single and multiple dosing. Methods Sixty-four healthy subjects were randomized to receive treatment and 56 completed the study. Groups of eight subjects each received voriconazole doses of 2 mg kg -1 twice daily, 4 mg kg -1 once daily, 2 mg kg -1 three times daily, or 3 mg kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
86
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 33 publications
9
86
1
2
Order By: Relevance
“…Voriconazole is a triazole antifungal with enhanced activity against a broad spectrum of fungal pathogens, including Aspergillus and Candida species (11, 26). We provide a succinct review of voriconazole's pharmacokinetics (PK) and present new PK-pharmacodynamic (PD) data relating drug concentration to therapeutic response.The pharmacokinetics of voriconazole in volunteers and patients have shown that voriconazole exhibits a nonlinear pharmacokinetic profile, secondary to saturable clearance (6,16,24,25). Voriconazole is metabolized by the cytochrome P450 system, with less than 2% of the dose excreted unchanged (12,13,24,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Voriconazole is a triazole antifungal with enhanced activity against a broad spectrum of fungal pathogens, including Aspergillus and Candida species (11, 26). We provide a succinct review of voriconazole's pharmacokinetics (PK) and present new PK-pharmacodynamic (PD) data relating drug concentration to therapeutic response.The pharmacokinetics of voriconazole in volunteers and patients have shown that voriconazole exhibits a nonlinear pharmacokinetic profile, secondary to saturable clearance (6,16,24,25). Voriconazole is metabolized by the cytochrome P450 system, with less than 2% of the dose excreted unchanged (12,13,24,25).…”
mentioning
confidence: 99%
“…The proportions of CYP2C19 extensive metabolizers in the U.S. population are estimated to be 2% homozygous extensive and 26% heterozygous extensive. Homozygous extensive metabolizers have a twofold lower exposure than heterozygous extensive metabolizers and fourfold lower drug exposure than poor metabolizers (12, 13).In 10 trials, the median values for the average and maximum voriconazole plasma concentrations in individual patients (n ϭ 1,121) were 2.51 g/ml and 3.79 g/ml, respectively (6,16,23,24,25). The values for area under the plasma concentrationtime curve on day 10 in 200-and 300-mg administration groups were approximately 5.8 and 3.8 times higher, respectively, among the poor metabolizers than among the extensive metabolizers.…”
mentioning
confidence: 99%
“…La absorción oral más elevada se obtiene con voriconazol, fármaco que administrado en ayunas alcanza una biodisponibilidad próxima al 100% [25][26][27], cifra que es inferior a su vez en el caso de itraconazol en solución (70%) [21], y que se reduce cuando este fármaco se administra en forma de cápsulas, hasta situarse en el 55%, cifra que es inferior cuando este fármaco se administra junto con una suspensión de alcalinos [18]. La biodisponibilidad de posaconazol, solo comercializado en solución para uso por vía oral, se sitúa en torno al 60% [10].…”
Section: Características Farmacocinéticasunclassified
“…Studies in both healthy volunteers [85][86][87] and critically ill adults [88,89] have demonstrated non-linear PK that is thought to be due to saturable first-pass metabolism and decreased systemic clearance. Consequently small changes in dose may affect large changes in serum drug levels.…”
Section: Pharmacologymentioning
confidence: 99%